Attempting to remedy sub-optimal medication adherence in haemophilia: The rationale for repeated ultrasound visualisations of the patient's joint status. (January 2019) - Di Minno, Alessandro; Spadarella, Gaia; Nardone, Antonio; Mormile, Mauro; Ventre, Itala; Morfini, Massimo; Di Minno, Giovanni
Abstract: Haemophilia is marked by joint bleeding (haemarthrosis) leading to cartilage damage (arthropathy). Lifelong prophylaxis—initiated after the first bleeding episode—leads to a dramatic decrease in arthropathy in haemophilia patients. However, adherence to continuous intravenous administrations of factor VIII (FVIII) or FIX products is challenging, and patients potentially suffer from breakthrough bleedings while on prophylaxis. Newer FVIII/FIX products with enhanced convenience attributes and/or easier infusion procedures are intended to improve adherence. However, pharmacokinetic data should be harmonised with information from individual attitudes and treatment needs, to tailor intravenous dosing and scheduling in patients who receive extended half-life products. Nor is there sound evidence as to how subcutaneous non-FVIII/FIX replacement approaches (concizumab; emicizumab; fitusiran) or single intravenous injections of adeno-associated viral vectors (when employing gene therapy) will revolutionize adherence in haemophilia. In rheumatoid arthritis, repeated ultrasound examination of a patient's major joints is a valuable tool to educate patients and parents to understand the disease and provide an objective framework for clinicians to acknowledge patient's adherence. Joint ultrasound examination in haemophilia significantly correlates with cartilage damage, effusion, and synovial hypertrophy evaluated by magnetic resonance imaging. Furthermore, in patients with haemophilia undergoing prophylaxis with an extended half-life product for a ≈ 2.8 year period, a significant continued improvement in joint health is detected at the physical examination. This provides the rationale for studies on repeated ultrasound examinations of joint status to attempt to remedy sub-optimal medication adherence and help identify which approach is most suited on which occasion and for which patient.